Social Capital: An Influence on Critical to Success Factors in Online Brand Communities. (2018) - Meek, Stephanie; Lambert, Claire; Ryan, Maria M.; Ogilvie, Madeleine
This study investigates the influence of social capital on the factors that are critical to continued participation in online brand communities (OBCs). The empirical investigation follows a structural equation modelling approach with data from 659 OBC members. Results indicate that social capital as a multidimensional construct represented by shared language, shared vision, social trust and reciprocity has a significant influence on an OBC members' participative behaviour, their sense of belonging (SOB), network ties, perceived enjoyment and perceived ease of use; all of which ensure longevity of the community. Consequently, stakeholders can use this information to develop strategies that will ensure the ongoing success of their OBCs.